Determinasi Pembiayaan Bermasalah Menggunakan Maqosid Syariah Index (Studi Terhadap BMT Di Kota Tasikmalaya) - Mardani, Dede Aji; Mahmudin, Wildan; Muflihah, Rini (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2023)
Baitul Mall Wa Tamwil (BMT) is a micro-level financial institution that operates as an intermediary for Muslim communities in particular and society in general for business sustainability and welfare. The purpose of this research is to analyze the factors that cause problematic financing at BMT in Tasikmalaya City using the Maqodid Syariah Index (MSI) method. The method used is qualitative with a descriptive concept where researchers go to the field by making observations, interviews involving seven BMT leaders in Tasikmalaya City. The approach method used is the Maqosid Syariah Index (MSI) which measures in terms of Tahzib Al Fardi, Iqamah Al Adalah, Jalb Al Maslahah. The results of this study indicate that BMT has difficulty in meeting its liquidity. There are two factors that cause problematic financing, namely internal factors including negligence of the financing examiner, the existence of a fraud attitude of employees, misappropriation of funds by the management, not using collateral, weaknesses in inspection and others. Meanwhile, external factors are customer defaults, lack of guidance and customer assistance, unwillingness to pay, bad business, fictitious domicile, the covid-19 epidemic which causes congestion in business. Even so, the BMT still considers the need for maqosid Sharia in running its business.